A Review of Pieces of Art from Sculptor Ferdinand Stuflesser’s Workshops in the Churches of the Archdiocese of San Jose, Costa Rica. - Bonilla Soto, Luis Carlos (2021)
Received: 24-12-2020. Approved: 05-04-2021. In the Costa Rican Church there is a marked tendency to exalt the works of sacred art. Specifically, the art brought to the country from the workshops of the sculptor Ferdinand Stuflesser and his descendants. This article is an effort of synthesis. It describes the location, themes, state of conservation and threats suffered by the various works from such acclaimed workshops.